Exploring Orthopedic Occupational Therapy in Korea: Insights from a Survey on Occupational Therapists’ Perspectives - Junghun Aj Kim (Occupational Therapy International)
This study explores the perceptions and experiences of Korean occupational therapists (OTs) about their role in managing elderly patients with orthopedic conditions. The goal is to inform policy discussions for better integration of OT services in orthopedic care settings in Korea. A survey was conducted among Korean clinical OTs to gather data on their perceptions, experiences, and challenges in providing orthopedic OT services. Snowball sampling was used, and the survey addressed general characteristics, orthopedic OT status, perceptions, and competence. The data were analyzed using frequency and percentage calculations in SPSS 22.0. Out of 171 respondents, only 18 had experience working in orthopedic departments, while 78 (45.6%) had provided occupational therapy to orthopedic patients. Rehabilitation medicine physicians were the primary prescribers of orthopedic OT. Key challenges included a lack of awareness among professionals, an absence of appropriate fees, and insufficient knowledge among OTs. The majority of respondents agreed that providing OT in orthopedic departments was appropriate and expressed a need for education and clinical guidelines. The study examines the current state of orthopedic OT in Korea, showing low levels of experience and highlighting challenges, such as a lack of professional awareness, inadequate fees, and insufficient knowledge among OTs. Respondents mostly agreed on the necessity for education and clinical guidelines to improve their capabilities in orthopedic settings. This study emphasizes the need for healthcare system improvements that allow OTs to participate more widely without being confined to specific medical disciplines, promoting a more comprehensive approach to OT, especially as the aging population continues to grow.